Patterns of taxonomic and functional diversity of termites along a tropical elevational gradient. (14th September 2016) - Nunes, Cássio A.; Quintino, André V.; Constantino, Reginaldo; Negreiros, Daniel; Reis Júnior, Ronaldo; Fernandes, Geraldo Wilson
Abstract: Patterns of termite richness along elevation gradients may be related to different responses by termite functional groups to changes in environmental conditions. We investigated the distribution of termite species richness along an elevational gradient of cerrado and rupestrian grasslands in the Espinhaço Mountain Range, in Brazil. Fifty termite species were recorded, with the family Termitidae being dominant; 16 species are endemic to open areas of cerrado and 1 species, Cortaritermes rizzinii, is endemic and restricted to mountaintop grassland habitats. Termite richness declined with increasing elevation, with the main factors associated with the reduction being climactic (air temperature, air and soil humidity, and radiation) and vegetation variables. Different termite communities were found along the elevational gradient, which were also strongly influenced by changes in climate and vegetation. On the other hand, the same functional groups were present at the different elevations, although represented by different species.